ONLINE ENGLISH CLASS ACTIVITIES DESIGNED ACCORDING TO REVISED BLOOM TAXONOMY - Nurul Frijuniarsi; Fitri Senny Hapsari (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Since the implementation of Learning from Home (LFH) policy, all of the learning activities are carried out online. Both lecturers and students have to deal with virtual class. As the organizer and facilitator, the lecturer in this case must be able to create not only efficient but also interesting class. The use of assistive media that can be accessed by both parties anytime, anywhere should be considered. This writing is composed in order to recommend some English course activities especially designed for online session. The activities are developed based on the Revised Bloom’s Taxonomy by utilizing the use of various applications and social media commonly used by students. The learning design is established in accordance with General English Course syllabus for first semester students in Informatics Engineering, Indraprasta University, yet it is also applicable for any classes that have the similarity on the learning target. Keywords: learning design, online learning, revised bloom taxonomy